Metformin alleviates spinal cord injury by inhibiting nerve cell ferroptosis through upregulation of heme oxygenase-1 expression - Zhihua Wang; Wu Zhou; Zhixiong Zhang; Lulu Zhang; Meihua Li (Neural Regeneration Research, 2024)
[INLINE:1] Previous studies have reported upregulation of heme oxygenase-1 in different central nervous system injury models. Heme oxygenase-1 plays a critical anti-inflammatory role and is essential for regulating cellular redox homeostasis. Metformin is a classic drug used to treat type 2 diabetes that can inhibit ferroptosis. Previous studies have shown that, when used to treat cardiovascular and digestive system diseases, metformin can also upregulate heme oxygenase-1 expression. Therefore, we hypothesized that heme oxygenase-1 plays a significant role in mediating the beneficial effects of metformin on neuronal ferroptosis after spinal cord injury. To test this, we first performed a bioinformatics analysis based on the GEO database and found that heme oxygenase-1 was upregulated in the lesion of rats with spinal cord injury. Next, we confirmed this finding in a rat model of T9 spinal cord compression injury that exhibited spinal cord nerve cell ferroptosis. Continuous intraperitoneal injection of metformin for 14 days was found to both upregulate heme oxygenase-1 expression and reduce neuronal ferroptosis in rats with spinal cord injury. Subsequently, we used a lentivirus vector to knock down heme oxygenase-1 expression in the spinal cord, and found that this significantly reduced the effect of metformin on ferroptosis after spinal cord injury. Taken together, these findings suggest that metformin inhibits neuronal ferroptosis after spinal cord injury, and that this effect is partially dependent on upregulation of heme oxygenase-1.